2022
DOI: 10.1002/eem2.12259
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Accelerates the Discovery of Two‐Dimensional Catalysts for Hydrogen Evolution Reaction

Abstract: Two‐dimensional materials with active sites are expected to replace platinum as large‐scale hydrogen production catalysts. However, the rapid discovery of excellent two‐dimensional hydrogen evolution reaction catalysts is seriously hindered due to the long experiment cycle and the huge cost of high‐throughput calculations of adsorption energies. Considering that the traditional regression models cannot consider all the potential sites on the surface of catalysts, we use a deep learning method with crystal grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…Performing the DFT calculation for such large combinations is practically impossible even with the fastest ab initio tools and is the primary cause for using ML in this work. Previously, the adsorption energy has been observed as a prominent descriptor for the catalyst’s activity. As the HER has a single electrochemical step and only one intermediate, the catalytic activity of a catalyst for HER is very much dependent on the adsorption energy of the catalyst. Moreover, adsorption energy descriptors are based on linear scaling relationships and linearly correlated with the activation energy through the Brønsted-Evans–Polanyi (BEP) relationships. Hence, it is a powerful tool for predicting trends in catalytic activity and screening new potential catalyst materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing the DFT calculation for such large combinations is practically impossible even with the fastest ab initio tools and is the primary cause for using ML in this work. Previously, the adsorption energy has been observed as a prominent descriptor for the catalyst’s activity. As the HER has a single electrochemical step and only one intermediate, the catalytic activity of a catalyst for HER is very much dependent on the adsorption energy of the catalyst. Moreover, adsorption energy descriptors are based on linear scaling relationships and linearly correlated with the activation energy through the Brønsted-Evans–Polanyi (BEP) relationships. Hence, it is a powerful tool for predicting trends in catalytic activity and screening new potential catalyst materials.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated the use of ML or deep learning (DL) methods to discover new HER catalysts like two-dimensional materials, 33 single-atom catalysts (SACs), 34 and nanoclusters. 35 In this work, we sought to intimately predict electrocatalyst surface material with the inclusion of coverage effect on the catalytic surface by exploiting density functional theory (DFT) along with ML methodologies to anticipate nonhazardous and economic heterogeneous catalyst alloys for HER.…”
mentioning
confidence: 99%
“…It is thus desirable to search for 2D materials with intrinsically active basal planes, which could naturally provide a much higher density of active sites. Our 2DMatPedia database includes around 3000 top-down 2D materials, providing a wealth of 2D materials for discovering high-performance HER candidates by high-throughput screening or machine-learning algorithms.…”
Section: Intelligent Data Mining Of Two-dimensional Functional Mateialsmentioning
confidence: 99%
“…From Materials Cloud, Karmodak et al screened out only 15 promising HER catalysts from 258 2D materials with E exf < 35 meV/Å 2 . For deeper data mining, Wu et al used a deep-learning method (at near-DFT accuracy) to screen out 38 high-performance HER catalysts from 6531 2D materials …”
Section: Other Publications Related To the 2dmatpedia Platformmentioning
confidence: 99%
See 1 more Smart Citation